Functioning of Civilian Hospitals in Cities of Tobolsk Province in 1870-1917 - A. I. Tatarnikova (Научный диалог)
The main aspects of the functioning of civilian hospitals in the cities of the Tobolsk province (city, prison, foreign, hospitals of the Orders of public charity, as well as small hospitals at some educational institutions) is discussed in the article. Based on the information contained in the reports of the Tobolsk Medical Board, as well as in the annual reviews of the province, changes are observed in the number of hospitals and medical personnel, the number of inpatient beds for several time sections. Attention is paid to the characteristics of hospital infrastructure, the material and technical and sanitary conditions of medical institutions. The conditions of stay of patients in medical institutions, issues of their nutrition are described. The conclusion is drawn about the increase in the costs of the central and local authorities for the organization of inpatient treatment during this period, as well as about the positive dynamics in the number of hospital facilities and medical staff in the cities of the specified province, qualitative changes in the organization of medical care for inpatients, and the improvement of their conditions in hospitals. The problems that arise in the functioning of hospital facilities in the cities of the province during the First World War are indicated.